Sequential Process of Diffusion Bonding and Annealing on Dissimilar Welding of Mg/Al Alloys - Yunlong Ding; Shixue Zhang; Bi Wu; Jinshuang Hao; Yan Chen; Dongying Ju (Advances in Materials Science and Engineering)
In this study, pressure supplying device based on thermal expansion and vacuum diffusion bonding method were used to weld magnesium alloy (AZ91) and aluminum alloy (6061). To enhance the microstructure and bonding properties of the welded Mg/Al alloys, the annealing process was continuously implemented on the composite specimens. Elemental analysis and structural observation/compound identification were conducted using an electron probe microanalyzer and a scanning electron microscope, respectively. For further assessment of the diffusion zone, microstructural examination was carried out using a transmission electron microscope. Furthermore, tensile strength and hardness values were also measured. The results showed that the diffusion zone widens with increasing annealing temperatures, but it changed obviously when the annealing temperature was 300°C. Intermetallic compounds in the diffusion zone were identified as Al2Mg and Al12Mg17, the microstructure and elemental composition were uniformly distributed, and tensile strength was the largest for the specimen annealed at 250°C. A possible reason for this could be that 250°C is nearly similar to the recrystallization temperature of Mg/Al alloys. Therefore, 250°C was determined to be the most suitable annealing temperature. In addition, the thermal expansion pressure supplying process was appropriate for the diffusion bonding of Mg/Al alloys.